Factors influencing limited repository access in academic libraries - Aliwijaya, Araf; Khoir, Safirotu (Berkala Ilmu Perpustakaan dan Informasi, 2025)
Introduction. Several academic libraries have implemented restrictions on repository access in recent years. This study explores the phenomenon of restricted access in academic libraries in managing their repositories. Method. This research uses a qualitative approach through interviews with six librarians from three academic libraries in the Special Region of Yogyakarta that have implemented repository access restrictions. Locations were selected through online observations of repository websites and direct. Library heads and staff involved in or understanding the access restriction process were selected purposively as informants. Data Analysis. The interview data were analyzed using reduction and thematic categorization techniques. The data were presented and analyzed to draw conclusions. Results and Discussion. Librarians, who generally support open access, face requests from faculty and university leadership to restrict access. Restrictions are implemented to protect intellectual rights and sensitive data, to maintain physical visits to the library. Other factors include concerns about plagiarism, personal data protection, patent rights, and preventing the illegal document distribution. Conclusion. There are eight factors in restricting access to academic library repositories. Access restrictions are based on the dynamic policies among stakeholders within the university. This study provides insights for academic library policymakers in balancing open access with intellectual property rights protection.